"It Has Been Brought to Completion" Leviticus 19:18 as Christological Witness in Galatians 5:14 - Suh, Michael K. W. (Journal for the study of Paul and his letters, 2012)
Paul's quotation of Lev 19:18 in Gal 5:14 is a curious appeal to the law at this point in the letter. Furthermore, his curious use of the perfect-passive verb πεπλήρωται to signal his citation of the Jewish Scriptures must be fully accounted for in order to understand Paul's view of the Torah in this section of Galatians. I will show that an intertextual reading of Gal 5:14 and Lev 19:18 can settle some of the interpretive issues in a coherent and satisfactory way. The hypothesis I propose is that Paul's quotation of Lev 19:18 resonates with the larger context of Lev 19, a text that asserts that the commandments of God are vitally connected with Yhwh himself. This resonance, in dialogue with the context of Gal 5:14, creates an intertextual space, whereby the identity of Jesus described by Paul in Galatians is parallel to the identity of Yhwh described in Leviticus. Therefore, Paul's use of πληρόω in Gal 5:14, followed by his citation of Lev 19:18, is his method of using Scripture as a dramatic witness to the person of Jesus Christ.